Agricultural industrial scale, price random fluctuation, and profitability levels: evidence from China’s pig industry - Yang, Qing; Qiao, Shiyan; Ying, Ruiyao (Frontiers in Sustainable Food Systems, 2024)
Using China's provincial panel data from 2003 to 2020 and the PVAR model for a dynamic study, the authors examine the dynamics correspond among price volatility, profitability levels and industrial scale. It also compares the reactions during disease risk and environmental regulation risk. This study finds an interactive relationship among price volatility, profitability levels and industrial scale, meaning industrial scale reduces not only random price fluctuations but also relative price. The negative impact on price volatility is more pronounced in medium-scale industry. The negative impact of profitability levels is more substantial in the medium-scale and large-scale industry. For producers, the high level of environmental regulation risk is not conducive to the healthy development of industrial scale and market prices. However, the industrial scale is more conducive to addressing the high disease risk.